KAJIAN TEOLOGIS TENTANG PENDIDIKAN AGAMA KRISTEN DALAM ALKITAB - Steven Tubagus (BONAFIDE: Jurnal Teologi dan Pendidikan Kristen, 2020)
With the development of liberal theology in the 18-19 century AD, there was an opinion that Christian Education was not in the Bible. This research aims to describe the study of the existence of Christian Education in the Bible. The method used is qualitative with a literature study. The research results are as follows: First, Christian Education in the Bible already exists in the Old Testament. God revealed Himself to the Israelites and gave teachings through the prophets. Second, the Old Testament centers on God's law, and God gave the Ten Commandments to the people of Israel as a basis for education. Third, in the New Testament of Jesus, Jesus' disciples and the early church always gave teachings as a manifestation of God's intervention.